Examining the term “Hybrid Warfare” within the Scope of Second Lebanon War and Russia’s Annexation of Crimea - Fırat Kaplan (Güvenlik Stratejileri Dergisi, 2023)
The term “Hybrid War”, which the security circles began to use frequently due to the Second Lebanon War and Russia’s annexation of Crimea in 2014, has not become a concept or doctrine accepted all over the world despite the passing years. Today, conflicts or tensions in the world can be explained by using the popularity of this term. As a result, there has been a tendency to explain the phenomenon of war, which is already hard to understand and comprehend on its own, by adding an adjective before it. However, to understand and analyse fully the reciprocal moves of the two warring actors, it is important not to overlook the fact that the actual courses of action of the warring parties may be hidden within the operation designs they made. In this context, the article analyses the Second Lebanon War, in which the term “hybrid war” emerged, and Russia’s annexation of Crimea, which increased the popularity of the term. Adopted qualitative research methodology, the article uses scientific research techniques such as centre of gravity analysis, discourse analysis, and hermeneutics. Secondary sources such as scientific books, articles, theses, and reports are used as basic data sources.